Genetic and phylogenetic analysis of canine bufavirus from Anhui Province, Eastern China - Wang, Yong; Guo, Xu; Zhang, Da; Sun, Jianfei; Li, Wei; Fu, Ziteng; Liu, Guangqing; Li, Yongdong; Jiang, Shudong (Infection, genetics and evolution, 2020)
Bufavirus is a novel virus associated with canine gastroenteritis. Three strains of bufavirus were first detected in dog feces collected from Anhui province in Eastern China. The near-complete genome sequences were amplified. Sequence alignment showed 98.3–99.5% homology between the three bufavirus strains and reference strains. Phylogenetic analysis showed the distributed viruses forming a cluster of close relationships. Selective pressure analysis of the VP2 region indicated that the canine bufavirus (CBuV) was mainly subject to negative selection during evolution. The negative selection site was located on the residue of B-cell epitopes, indicating minimal change to the virus's immunogenicity. Since this is the first report of CBuV circulating in Anhui Province, this study will provide further understanding of the phylogenetic and molecular characteristics of CBuV and serve as a reference for prevention and vaccine development. •Molecular evidence was found for the prevalence of canine bufavirus in Anhui province.•The canine bufavirus was evolutionarily conservative.•Canine bufavirus was mainly subject to negative selection, and part of the site coincides with the B-cell epitope.